Understanding vocabulary of L2 learners of Japanese - Moritoki Škof, Nagisa (Acta linguistica asiatica, 2023)
The analysis of this study aims to investigate the effectiveness ofreading skills manifested by L2 learners of Japanese. In order to analyze the reading process of L2 learners of Japanese, we analyzed the data of 24 non-kanji learners of Japanese that were obtained fromthe “Reading corpus of non-native speakers of Japanese.”Using Yang’s (2006) categorization, weanalyzedlearners’understandingof wordsin the text through two different situations, (1) when they lack the relevant language skills, and (2)when they encounter unknown words while reading a text. The results show that learners use various tools,dependingon the purpose,to find appropriate meaningsof individualwordsand to understand the meaningsof whole sentencesand texts. Also, the results suggest that appropriate language knowledge prevents incorrect assumptions in comprehension and supports successful comprehension ofwhole texts.
Keywords: besedni pomeni; bralne strategije; bralno razumevanje; comprehension monitoring strategies; L2 learnerof Japanese; language knowledge; reading comprehension; reading strategies; strategije spremljanja razumevanja; učenec japonščine kot tujega jezika; vocaburaly meanings; znanje jezika